Pengaruh Pendayagunaan Zakat Produktif Terhadap Pemberdayaan Mustahiq Studi Pada Badan Amil Zakat Jawa Timur - Afriansyah, Dhaniar (Universitas Negeri Surabaya, 2020)
This study aims to determine the effect of the Utilization of Productive Zakat with Empowerment of Mustahiq in the Amil Zakat Board in East Java. The research uses a quantitative approach. The number of samples used in this study amounted to 33 respondents who came from the Badan Amil Zakat East Java mustahiq who owns a business. Tthe analysis technique used to use simple regression analysis. Based on the results of his study using the t test utilization of productive zakat known value of this variable is -1278 means that smaller and positive values of t table that is equal to 2,040 which is obtained from the distribution of value table and significance value 211, it can be concluded that the utilization productive zakat affects the empowerment mustahiq